Direito ao esquecimento no Brasil: busca de parâmetros estruturantes para a ponderação de princípios - Toledo, Juliana Amaral (2024)
Technological evolution and the dynamics of human relationships and manifestations in the digital environment demonstrate the need to study the right to be forgotten, considering the new contours of privacy, the implications of the capacity to store an increasing number of data and information shared about individuals and the expansion of memory by digital media over time. The massive use of data and profiling in the digital world, enhanced by the use of increasingly efficient algorithms and artificial intelligence tools, makes us vulnerable, especially in relation to our intimacy and honour, our freedom to determine who we are. This thesis is therefore conceived with a view to reflecting on the right to be forgotten, given its instrumental nature in safeguarding important individual freedoms and rights. The aim of this work is to encourage discussions on the right to be forgotten in Brazil and to identify parameters for weighing up principles, structuring a decision-making matrix capable of guiding decisions involving this right. To this end, bibliographical research is used as a methodological strategy, with books, scientific articles, research reports, newspaper and magazine articles, and recent Brazilian and foreign case law on the subject being considered as the documentary corpus. The research findings are described in the chapters developed, which are: 1) Challenges of the Information Society; 2) The Right to be Forgotten in Brazilian Courts; and 3) The decision-making matrix of cases involving the right to be forgotten: the meta-principle of human dignity as a hermeneutic criterion for settling hard cases. In the first chapter, the challenges of the information society are highlighted, and the discussion about aspects concerning the right to be forgotten in the context of today's society takes place. The need for data protection in the surveillance society is emphasized, and the rights to freedom of expression and privacy are pointed out as fundamental rights. The first chapter also brings some reflective contributions from foreign law. The next chapter is dedicated to the right to be forgotten from the point of view of the ways in which it can be exercised in the light of the Brazilian courts. It discusses the process of formulating the General Repercussion Theme, which determined the unconstitutionality of the right to be forgotten in this specific case. However, this chapter points out that the issues and interests involved in the discussion on the right to be forgotten are broader than those considered by the Supreme Court. Finally, in the last chapter of the thesis, the structuring elements that make up the broad concept of the right to be forgotten in the face of the interests being weighed up, as per the General Repercussion Theme 876 of the Brazilian Supreme Court, are identified, highlighting the constituent elements of the rights to freedom of expression, privacy and to be forgotten. After all, a decision- making matrix has been developed, capable of fostering and guiding decision-making on the right to be forgotten, pointing to the meta-principle of human dignity as its guiding principle. This thesis is part of research line 1 of UNINOVE's Postgraduate Law Programme, called ‘Structures of Business Law’, Research Project 1: ‘Freedoms and Economic Power in Capitalism’.